PENDEKATAN EKONOMI TERHADAP RESTITUSI DALAM TINDAK PIDANA YANG DILAKUKAN OLEH ANAK - La Ode Dedi Abdullah; Endang Tri Pratiwi; Jamil Jamil (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the regulation and implementation of restitution in juvenile criminal offenses and examine it from an economic law perspective. The findings indicate that although restitution is normatively recognized within the Juvenile Criminal Justice System, its regulation remains partial and not comprehensive. This situation results in suboptimal implementation in practice, preventing the full achievement of child protection, victim rights restoration, and restorative justice objectives. Therefore, regulatory strengthening and harmonization are required to ensure effective and equitable application of restitution. From an economic law perspective, restitution serves as an effective and efficient instrument, capable of compensating victims’ losses while reducing the social costs associated with penal sanctions. However, its application still faces constraints due to normative regulatory limitations. Consequently, a more integrated restitution framework is necessary so that economic efficiency aligns with child protection and the realization of restorative justice goals.